Toward an Evaluation Model of User Experiences on Virtual Reality Indoor Bikes - Sun-Uk Kim; KyunJoo Lee; Jae-Hyung Cho; Kyo-Chan Koo; Se Beom Kim (European Scientific Journal, ESJ, 2017)
This paper deals with deriving a model or framework to evaluate user experiences (UX) of virtual reality (VR) systems, especially, VR indoor bikes which are under construction. Recently, VR is one of the most appealing areas attracting people’s interests around the world. Many products armed with it increasingly emerge on the market, and it is expected that the use of VR systems will continue to increase sharply in the future. However, UX of such products cannot be evaluated appropriately at the moment due to a lack of proper evaluation models. In a broad sense, UX that may stem from human machine interface in ergonomics covers affect, usability, and user value in spite of some differences in definition among the researchers. While evaluations of UX on the products without VR have been overall justifiably performed, UX has been evaluated neither systematically nor strictly on the products with VR. Through the analyses of expert reviews, we newly identify an additional component and its elements, and modify some elements of the three existing components for evaluating UX on the VR systems. As a result, we propose a comprehensive evaluation model of UX, which consists of four factors: usability, affect, user value, and presence feeling. In addition, we determine the components and their elements for specific VR indoor bikes similarly through the analyses of expert surveys and focus-group discussions, which results in developing a questionnaire for users. Finally, along with the questionnaire, we propose a specific evaluation model for VR indoor bikes.